Lower vitamin D levels are associated with depression in patients with gout - Zhou Q (Dove Medical Press, 2019)
Qiang Zhou, Yi-chuan Shao, Zheng-qi Gan, Li-shu Fang Department of Endocrinology, First Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang Province, China Background: Depression is commonly observed among patients with gout. Low levels of vitamin D have been associated with depression in non-gout subjects. We examined the association of vitamin D levels with depression in patients with gout. Methods: We conducted a cross-sectional study of 186 gout patients at the Endocrinology Department of First Affiliated Hospital of Jiaxing University. Levels of serum 25-hydroxyvitamin D (25(OH)D) were determined using a competitive protein-binding assay. The 17-item Hamilton Depression Scale was used for screening for depressive symptoms. Diagnosis of depression in gout patients was made in accordance with Diagnostic and Statistical Manual of Mental Disorders, fifth edition criteria for depression. Multivariate analysis was performed using logistic regression models. Results: Thirty-two gout patients (17.2%) were diagnosed as having depression. Patients with depression showed significantly lower 25(OH)D levels as compared to patients without depression (46.4±19.0 vs 57.0±17.3 nmol/L, P<0.001). Significant differences in 25(OH)D quartiles of gout patients were observed between the patients with depression and the patients without depression (P=0.003). In multivariate analyses, serum 25(OH)D levels (≤40.0 nmol/L) were independently associated with depression in patients with gout (OR 3.833, 95% CI 1.406–10.453, P=0.009). Conclusion: Our study demonstrates an important association between serum vitamin D levels and depression in patients with gout. Keywords: depression, vitamin, gout